2017
DOI: 10.1158/1055-9965.epi-16-0706
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Survival Disparities Between First Nation and Non-Aboriginal Adults in Canada: Follow-up of the 1991 Census Mortality Cohort

Abstract: The results of this study can serve as a benchmark for monitoring progress toward narrowing the gap in survival. Cancer Epidemiol Biomarkers Prev; 26(1); 145-51. ©2016 AACR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 42 publications
1
46
0
1
Order By: Relevance
“…Certain confounding factors such as diet, lifestyle (consumption of fruits, vegetables, red meat, salt, cigarettes, and alcohol, and physical activity), socioeconomic status, place of residence, race, health insurance, and Helicobacter pylori infection have been shown to play paramount roles in gastric cancer development [ 31 , 32 , 33 , 34 , 35 ]. Conversely, the data available for our ecological analysis were based on population-level information and were insufficient to propose a multilevel analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain confounding factors such as diet, lifestyle (consumption of fruits, vegetables, red meat, salt, cigarettes, and alcohol, and physical activity), socioeconomic status, place of residence, race, health insurance, and Helicobacter pylori infection have been shown to play paramount roles in gastric cancer development [ 31 , 32 , 33 , 34 , 35 ]. Conversely, the data available for our ecological analysis were based on population-level information and were insufficient to propose a multilevel analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, all cancer incidence and mortality rates are lower in US Asian, Native Hawaiian and Pacific Islanders in the US 4 , and in UK East Asians and South Asians 3 when compared with Whites. North American indigenous populations such as American Indians and Canadian First Nations have a risk of cancer death significantly higher than that for Whites, despite regional variation 1,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…These results provide evidence to support culturally appropriate risk-reduction strategies to reduce the burden of potentially avoidable cancers, emphasizing tobacco prevention and cessation, healthy body weight, and regular participation in cancer screening. Given the increased incidence of cancer observed in this study, and poorer survival observed in our earlier study of the same First Nations cohort (Withrow et al 2017), efforts to improve access to cancer treatments including traditional healing methods are also warranted. This study also found significantly lower incidence for various cancer types among First Nations people, for which additional research is warranted to investigate possible contributing factors.…”
Section: Resultsmentioning
confidence: 78%
“…Cancer is the second leading cause of death among First Nations women and ranks third among First Nations men (Tjepkema et al 2009). Our previous report noted poorer cancer survival for First Nations compared to non-Aboriginal adults in Canada for most cancer types (Withrow et al 2017). Cancer patterns between First Nations and non-Aboriginal adults in Canada are understudied, primarily due to a lack of ethnic identifiers in cancer registries.…”
Section: Introductionmentioning
confidence: 92%